Integration of Sharia Principles in Islamic Hospital Management: Opportunities and Obstacles - Astiwara, Endy Muhammad (GoAcademica Research & Publishing, 2024)
This study aims to explore the opportunities and barriers in integrating sharia principles into Islamic hospital management. Such integration is not only important in clinical aspects, but also at managerial levels such as finance, human resources, strategic decision-making, and governance. This study analyzed 40 scientific articles published between 2013 and 2024 using the Systematic Literature Review (SLR) approach, collected through the Scopus, ScienceDirect, and Google Scholar databases. Data analysis was carried out with the help of NVivo software to identify key themes that emerged consistently in the literature. The results showed that integration opportunities arise from the increasing awareness of the Muslim community, the need for service differentiation, and the compatibility of sharia values ​​with modern management principles. Significant barriers remain, such as the lack of human resources who understand sharia management, the absence of international standard standards, and dualism of regulations between medical and sharia. This study also presents case studies and provides practical recommendations for hospital managers, academics, and policy makers in strengthening the implementation of sharia-based management systematically and sustainably.